Darwin and human evolution: origin of species revisited - International Seminar on Darwin and Human Evolution (2010 : Asiatic Society); Ray, ranjana; Chattopadhyay, Dhrubajyoti; Banerjee, Samir; Asiatic society (Kolkata) (Kolkata : Asiatic Society, 2014)
Papers presented at the International Seminar on Darwin and Human Evolution, held at Asiatic Society during 10-12 February 2010
Includes bibliographical references
Keywords: Evolution; Evolution (Biology)